The stomach cancer pooling (StoP) project. Issue 1 (January 2015) - Pelucchi, Claudio; Lunet, Nuno; Boccia, Stefania; Zhang, Zuo-Feng; Praud, Delphine; Boffetta, Paolo; Levi, Fabio; Matsuo, Keitaro; Ito, Hidemi; Hu, Jinfu; Johnson, Kenneth C.; Ferraroni, Monica; et al.
<x xml:space="preserve">Abstract</x> Gastric cancer affects about one million people per year worldwide, being the second leading cause of cancer mortality. The study of its etiology remains therefore a global issue as it may allow the identification of major targets, besides eradication of Helicobacter pylori infection, for primary prevention. It has however received little attention, given its comparatively low incidence in most high-income countries. We introduce a consortium of epidemiological investigations named the 'Stomach cancer Pooling (StoP) Project'. Twenty-two studies agreed to participate, for a total of over 9000 cases and 23 000 controls. Twenty studies have already shared the original data set. Of the patients, 40% are from Asia, 43% from Europe, and 17% from North America; 34% are women and 66% men; the median age is 61 years; 56% are from population-based case–control studies, 41% from hospital-based ones, and 3% from nested case–control studies derived from cohort investigations. Biological samples are available from 12 studies. The aim of the StoP Project is to analyze the role of lifestyle and genetic determinants in the etiology of gastric cancer through pooled analyses of individual-level data. The uniquely large data set will allow us to define and quantify the main effects of each risk factor of interest, including a number of infrequent habits, and to adequately address associations in subgroups of the population, as well as interaction within and between environmental and genetic factors. Further, we will carry out separate analyses according to different histotypes and subsites of gastric cancer, to identify potential different risk patterns and etiological characteristics.